Stick together and come back home : racial sorting and the spillover of carceral identity - Lopez-Aguado, Patrick (University of California Press, 2018)
"The distinction between the consequences of an act and the act itself is supposed to define the fight between consequentialism and deontological moralities. This book, though sympathetic to consequentialism, aims less at taking sides in that debate than at clarifying the terms in which it is conducted. It aims to help the reader to think more clearly about some aspects of human conduct--especially the workings of the 'by'-locution, and some distinctions between making and allowing, between act and upshot, and between foreseeing and intending (the doctrine of double effect). It argues that moral philosophy would go better if the concept of 'the act itself' were dropped from its repertoire. Book Keywords: action, allowing, consequences, consequentialism, deontological ethics, double effect, ethics, intention."--Provided by publisher.